About the kinetics of the emulsion layer growth at the liquid–liquid boundary under the conditions of controllable convection. - E. V. Eskova; G. A. Grigoriev; M. C. Eskov (Тонкие химические технологии)
The kinetics of the interface layer growth was considered for the case of interaction of oleic acid with alkali. The temperature dependence of the microemulsion growth was studied. Effective activation energies of complicated heterogenic processes were determined.